Scintillation and photoluminescence investigations of Gd2MoB2O9: CeF3 phosphors. (October 2022) - Wongwan, W.; Yasaka, P.; Boonin, K.; Angnanon, A.; Duangjai, K.; Sa-ardsin, W.; Kothan, S.; Kaewkhao, J.
Abstract: The CeF3 doped Gd2-x MoB2 O9 phosphors (where x = 0.00, 0.25, 0.50 and 0.75 mol%) were synthesized by the conventional high-temperature solid-state reaction method at 900 °C for 12 h in air. DSC and TGA analysis executed to study the optimum temperature for sintering. The structural, photoluminescence and X-ray luminescence properties were investigated. The structure of the samples was analyzed by using X-ray diffractometer (XRD). The absorption spectra were analyzed and found that absorption edge increased with the increasing concentration of CeF3 . The photoluminescence of phosphors shows the overlapping of excitation and emission peaks in the range of 300 nm–450 nm. These emission peak correspond to the 5d – 4f transitions of Ce 3+ ion. The optimum concentration of CeF3 in these phosphors is 0.50 mol% corresponding to maximum emission intensity. The X-ray induced optical luminescence spectra showed a strong emission peak at 411 nm the concentration quenching at 0.75 mol%, which is as efficient as 54.4% compared with bismuth germanium oxide (BGO) crystal. The luminescence decay increased with the increment of CeF3 concentration. From the optical properties investigated, it was found that the phosphors performed a strong and fast luminescence signal which is appropriate for the development of scintillators in X-ray detector devices. Highlights: Synthesis of phosphors doped Ce 3+ ion for photonic and scintillation materials applications. The strong emission spectra at 411 nm were observed. The Decay time of the phosphors with the highest emission intensity (5d .→ 4f transition) was 12.35 ns Highest X-ray-induced luminescence intensity is 411 nm of Ce 3+ ion at the 5d .→ 4f transition. The integral scintillation efficiency of phosphors was 54.44% of the BGO crystal.